Application of The Concept of Mathematical Limits In The Quranic Verse of Yusuf Verse 76: Text And Context Analysis - Azhar, Aurizan Himmi; Nurhuda, Abid; Lathif, Nur Muhammad (ARMADA : Jurnal Penelitian Multidisiplin, 2025)
This article explores the relationship between the concept of limits in mathematics and the verse (QS. Yusuf: 76), which emphasizes that above every knowledgeable person there is one who is more All-Knowing. The limit in calculus describes an endless process of approximation, where a function approaches a certain value without ever actually reaching it. This concept has a philosophical correlation with the teachings of the Qur'an that emphasize intellectual humility and the awareness that human knowledge is always limited compared to God's knowledge. Through a textual and contextual analysis approach, this article examines how the verse is understood by classical and contemporary commentators and interprets it within the framework of modern mathematical epistemology. The analysis finds that both the concept of the limit and the content of the verse teach that the pursuit of knowledge is a continuously evolving process without an endpoint. Thus, the collaboration between science and sacred texts can open a new paradigm in understanding the relationship between mathematical rationality and divine spirituality.